The impact of the COVID-19 pandemic on the quality of life and stress of teachers in a federal institution (Research, Society and Development, 2021)
The SARS-CoV-2 pandemic declared by the World Health Organization in 2020 imposed on the population a change in attitudes and adaptation in ways of life in all contexts. Considering that such changes may reflect negatively on people's lives, this research aims to determine the impact of the COVID-19 pandemic on the quality of life and stress of teachers in basic, technical and technological education at a federal educational institution. This is a cross-sectional epidemiological study, whose data collection occurred remotely, in the months of September to November 2020 through the application of an instrument of sociodemographic, training and occupational identification, developed by the authors, the WHOQOL -bref, Brazilian version and Lipp's Stress Symptoms Inventory. The results were obtained through descriptive and inferential analysis and showed a 61.14% General Quality of Life Index (IGQV). The marital situation, the fact of having children, participating in commissions and having a maximum degree was significantly associated with the physical, psychological, social relations and general domains, respectively. In the stress assessment, 54.95% had a positive assessment with predominance in the resistance phase (90%), with psychological symptoms (66%) and significant association in all domains of the WHOQOL-bref, demonstrating that stress interferes with quality of life of teachers. Thus, the importance of promoting actions that aim to reduce stress levels to improve the quality of life of teachers is highlighted.